PREPARATION SYSTEMS OF CALCIUM AND MAGNESIUM BASED PRODUCTS FROM THE LEACHING SOLUTION CONTAINING CALCIUM AND MAGNESIUM OF A CO2-BASED HYDROMETALLURGICAL PROCESS - ZHOU, Xiaozhou; ZHAO, Huangjing (2021)
The present invention discloses the systems of producing calcium and magnesium carbonate from the Ca/Mg containing solution leached by a CO2-based hydrometallurgical process which includes: a precipitation reactor that the Ca/Mg containing leached solution is continuously added and fully mixed with the alkaline reagent at specific mole ratio into the precipitation reactor and the reactor also comprises a CO2 bubbling module where CO2 is captured and recirculated from the thermal decomposition process as needed; a solid-liquid separation unit that the treated slurry is treated by the solid-liquid separation unit to produce precipitated calcium and magnesium carbonate products where the recirculating water is recycled back into the precipitation reactor; a thermal decomposition unit that the calcium and magnesium carbonate products is calcined by the thermal decomposition unit to produce an alkaline reagent and the alkaline reagent is recycled back into the precipitation reactor for the next batch of reaction.